Phenethyl isothiocyanate inhibits metastasis potential of non-small cell lung cancer cells through FTO mediated TLE1 m6A modification - Zhang Qi-cheng; Qian Yong-mei; Ren Ying-hui; Chen Meng-meng; Cao Li-min; Zheng Si-jia; Li Bing-bing; Wang Min; Wu Xiang; Xu Ke (Acta Pharmacologica Sinica, 2024)
N6-methyladenosine (m6A) modification is a prevalent RNA epigenetic modification, which plays a crucial role in tumor progression including metastasis. Isothiocyanates (ITCs) are natural compounds and inhibit the tumorigenesis of various cancers. Our previous studies show that ITCs inhibit the proliferation and metastasis of non-small cell lung cancer (NSCLC) cells, and have synergistic effects with chemotherapy drugs. In this study, we investigated the molecular mechanisms underlying the inhibitory effects of ITCs on cancer cell metastasis. We showed that phenethyl isothiocyanate (PEITC) dose-dependently inhibited the cell viability of both NSCLC cell lines H1299 and H226 with IC50 values of 17.6 and 15.2 μM, respectively. Furthermore, PEITC dose-dependently inhibited the invasion and migration of H1299 and H226 cells. We demonstrated that PEITC treatment dose-dependently increased m6A methylation levels and inhibited the expression of the m6A demethylase fat mass and obesity-associated protein (FTO) in H1299 and H226 cells. Knockdown of FTO significantly increased m6A methylation in H1299 and H226 cells, impaired their abilities of invasion and migration in vitro, and enhanced the inhibition of PEITC on tumor growth in vivo. Overexpression of FTO promoted the migration of NSCLC cells, and also mitigated the inhibitory effect of PEITC on migration of NSCLC cells. Furthermore, we found that FTO regulated the mRNA m6A modification of a transcriptional co-repressor Transducin-Like Enhancer of split-1 (TLE1) and further affected its stability and expression. TCGA database analysis revealed TLE1 was upregulated in NSCLC tissues compared to normal tissues, which might be correlated with the metastasis status. Moreover, we showed that PEITC suppressed the migration of NSCLC cells by inhibiting TLE1 expression and downstream Akt/NF-κB pathway. This study reveals a novel mechanism underlying ITC’s inhibitory effect on metastasis of lung cancer cells, and provided valuable information for developing new therapeutics for lung cancer by targeting m6A methylation.